Il vertice EAASI: l'evento più importante dell'anno per l'industria del rilevamento aereo in Europa (GEOmedia, 2023)
The European Association of Aerial Surveying Industries (EAASI) closed a successful edition of its Partners Summit last 2 December.More than 70 representatives from 40 companies connected to the aerial surveying industry gathered in Rome for 3 days to discuss the current challenges of the industry as well as explore new business opportunities.The participants attended a series of presentations, panel discussions, and workshops covering a wide range of topics such as climate change, digital twins, or certification and standardization, among others.